Transit-oriented development: a case study of Rosebank, City of Johannesburg - Baylis, Michael Leighton (Department of Civil Engineering, 2017)
The use of the Transit Oriented Development (TOD) concept is commonplace in many South African municipal spatial development frameworks aimed at guiding future urban development towards more compact and efficient forms. The indication is that the achievement of planned TOD (i.e. where there is an approved spatial development framework), an area of high density, mixed land use served by car-competitive public transport services, is often hampered by the absence of aligned policies and other factors that would help achieve success. This research looks into these policies and success factors, and more specifically considers whether parking provision and management in such areas is a critical component in achieving or discouraging modal change from private car usage to public and non-motorised movement and the achievement of a desirable high density live-and-work environment. It uses the long-established Rosebank Regional Node in the City of Johannesburg and the approved Rosebank Urban Development Framework, 2008, ("RUDF") as a case study, quantifying the spatial planning proposals and identifying possible shortcomings in the implementation of the TOD in this existing suburban area, now served by a Gautrain Station. The quantification of the RUDF proposals serves to identify the proposed land uses within the node and facilitates the application of the relevant parking standards and trip generation factors applicable to each, thereby illustrating the traffic demand on the road network as well as the parking to be supplied if current parking policies are adhered to. These are then compared the road network's capacity to identify mismatches. The research shows that the current practice of promoting densification while applying the standard parking suburban regulations (drafted in 1979) will not achieve a less private-cardependent lifestyle, and that without integrating parking policy and traffic demand management into the planning strategy, the likelihood is that the TOD vision will fail.